2002
DOI: 10.1097/00005053-200203000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Observations of Emerging Psychosis

Abstract: Because delays in treatment of psychosis may be associated with poorer outcomes, intervention focus has shifted to the prodromal phase of illness. However, knowledge about this phase has been limited to retrospective reconstructions of symptoms once psychosis is already present. The following article offers a new, prospective view of the development of schizophrenia starting from the late prodromal phase of illness. As we use the term, late prodromal phase of illness means at imminent risk of conversion to sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…UHR syndromes were diagnosed using the Structured Interview for Prodromal Symptoms (SIPS; McGlashan et al, 2001; Miller et al, 2003; Rosen et al, 2002). The Structured Clinical Interview for DSM-IV (SCID; First et al, 1995) ruled out psychotic disorders.…”
Section: Methodsmentioning
confidence: 99%
“…UHR syndromes were diagnosed using the Structured Interview for Prodromal Symptoms (SIPS; McGlashan et al, 2001; Miller et al, 2003; Rosen et al, 2002). The Structured Clinical Interview for DSM-IV (SCID; First et al, 1995) ruled out psychotic disorders.…”
Section: Methodsmentioning
confidence: 99%
“…This period of emerging symptom presentation commonly develops into a pre-psychosis prodromal state on the continuum from normal cognition toward schizophrenia (see Moller, 2001). During childhood and this prodrome, neuropsychological impairments may be phenotypic markers of increasingly compromised brain organization, eventually leading to psychosis (Rosen, Woods, Miller, & McGlashan, 2002). Morphological studies of schizophrenic patients early in their disorders also lend support for developmental theories of schizophrenia.…”
Section: Schizophreniamentioning
confidence: 95%
“…However, a series of groundbreaking studies carried out by researchers at the University of Melbourne demonstrated that it may be possible to identify a group of young people at ultra high-risk of becoming psychotic in the immediate future (Yung et al, 1998). Trials of preventative therapy for this ultra high-risk group are already under way in Australia (McGorry et al, 2001) the United States (Rosen et al, 2002), and in Britain (where the authors are close to completing a small clinical trial; (Morrison et al, in press).…”
mentioning
confidence: 99%
“…Most of the ongoing studies have employed an atypical neuroleptic for this purpose, either in combination with psychological therapy (for example, in the first study completed in Melbourne (McGorry et al, 2001), or alone (for example, in the ongoing PRIME trial in North America, Rosen et al,2002) or have sought to compare the efficacy of an atypical neuroleptic with the efficacy of psychologica l treatment (as in a trial currently planned at the Institute of Psychiatry). If the results of these studies are successful in crude terms -if the participants who are treated experience fewer psychotic episodes at follow-up than those who do not -the pressure to use this kind of treatment in clinical services may prove almost irresistible.…”
mentioning
confidence: 99%